Advancements of physical exercise and intestinal microbiota and their potential mechanisms - Li, Rendong; Zhang, Tianning; Cheng, Zhen; Yao, Chenxi; Meng, Xiangguang; Ma, Tie (Frontiers in Microbiology, 2025)
Gut microbiota is closely related to body functions. At present, evidence has shown that gut microbiota and its metabolites interact with exercise, but the effects and related mechanisms are still in the exploratory stage. Therefore, this paper summarizes the results of experiments related to exercise and gut microbiota, and analyzes the possible mechanism of the interaction between the two, in order to provide a theoretical basis for further research on the relationship between exercise and gut microbiota. The intervention of gut microbiota may be an effective help to improve exercise capacity. The abundance, composition and diversity of gut microbiota can affect the body’s exercise quality. We conclude, the relationship between exercise and gut microbiota is closely related and not only determined by a single influencing mechanism, which provides a new perspective and direction for future research on the relationship between exercise and gut microbiota.